Knowledge Creativity and The Sustainability of Public Hospitals In South-South Nigeria: A Regression Analysis - Julius Agba Ada; Pius U. Angioha (SAINSMAT: Journal of Applied Sciences, Mathematics, and Its Education, 2021)
The specific objective of the study was to ascertain the extent to which knowledge creativity influences the sustainability of public hospitals in South-South Nigeria. The study employed a correlation design. A sample of 596 respondents was selected from twelve categorized public hospitals in South-South, Nigeria. Thirty-four questions were formulated in the questionnaire in line with the stated objective of the study. A total of 596 copies of the questionnaire were administered, and 551 copies were collected, showing 92 per cent responses, ten responses were rejected, and 541 documents constituting 90 per cent of the questionnaire were analyzed. The results showed a significant positive relationship between knowledge creation and sustainability of public hospitals in South-South Nigeria. The study concluded that knowledge creativity is a tool to facilitate healthcare organizational performance and productivity towards quality service delivery. The study, therefore, recommends that the administrators in healthcare organizations should be mindful that adoption of knowledge management practices would be dependent on leadership, information technology, infrastructure, organizational behaviour and supporting policies of human resource management.